Compensating teachers serving rural schools: evidence from a developing region in southern China - Hongmei Ma; Wanpeng Lei (Humanities & Social Sciences Communications)
Abstract Desirable working conditions such as geographic accessibilities attached to the job are important amenities for individuals to maximize their occupational utility, and the absence of comfortable working conditions should be equally and adequately compensated. The “compensating wage differential” hypothesis subsumed by hedonic wage theory offers us the theoretical framework to interpret the relationship between individuals’ earnings and job dis(amenities). In the teacher labor market, job disamenities such as the undesirable geographic location of schools should be compensated to balance the spatial distribution of teachers. The authors tested this idea by employing a unique self-collected dataset, sourced from a representative developing region in southern China. The results showed that teachers’ earnings were positively associated with the geographical unpopularity attached to the rural school where they worked, holding other factors constant. In addition, the result yielded by instrumental variable identification strategy confirmed that teachers’ positive self-selection into rural schools had led to an underestimation of the adverse impact of geographic ruralness on their utility losses. This paper sheds light on how to staff schools located in geographically disadvantaged areas with quality teachers by properly offering economic incentives.